2012
DOI: 10.1016/j.seppur.2011.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a fluid dynamics based model of the UF Falcon concentrator in the ultrafine range

Abstract: Experimental validation of a fluid dynamics based model of the UF Falcon concentrator in the ultrafine range . (2012) Separation and Purification Technology, vol. 92. pp. 129-135. ISSN 1383-5866 Open Archive Toulouse Archive Ouverte (OATAO)OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.Any correspondence concerning this service should be sent to the repository administrator: staff-oatao@inp-toulouse.fr The process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 10 publications
2
6
0
1
Order By: Relevance
“…These results confirm those obtained by Kroll-Rabotin et al (2012) with pure quartz, who showed that the tailings PSD remains unchanged for the first few minutes of the separation and then shifts towards the PSD of the feed [22]. This first phase of the separation during which ultrafine particles are rejected with a relatively constant PSD was taken to be a proof that the Falcon UF operates a steady state separation until the retention zone is full [22]. While it may be true for pure minerals, it seems that the opposite is observed here with more complex materials such as the industrial ores used in this study, exhibiting more heterogeneous compositions comprising high density metal-bearing minerals and gangue minerals displaying a range of low to medium specific gravities (Table 1).…”
Section: Particle Size Effectssupporting
confidence: 92%
See 3 more Smart Citations
“…These results confirm those obtained by Kroll-Rabotin et al (2012) with pure quartz, who showed that the tailings PSD remains unchanged for the first few minutes of the separation and then shifts towards the PSD of the feed [22]. This first phase of the separation during which ultrafine particles are rejected with a relatively constant PSD was taken to be a proof that the Falcon UF operates a steady state separation until the retention zone is full [22]. While it may be true for pure minerals, it seems that the opposite is observed here with more complex materials such as the industrial ores used in this study, exhibiting more heterogeneous compositions comprising high density metal-bearing minerals and gangue minerals displaying a range of low to medium specific gravities (Table 1).…”
Section: Particle Size Effectssupporting
confidence: 92%
“…These results confirm those obtained by Kroll-Rabotin et al (2012) with pure quartz, who showed that the tailings PSD remains unchanged for the first few minutes of the separation and then shifts towards the PSD of the feed [22]. This first phase of the separation during which ultrafine particles are rejected with a relatively constant PSD was taken to be a proof that the Falcon UF operates a steady state separation until the retention zone is full [22].…”
Section: Particle Size Effectssupporting
confidence: 90%
See 2 more Smart Citations
“…R min , R max and H bowl define the bowl geometry (base radius, radius at the outlet and height) and λ is a calibration constant. Experiments yielded a value of λ = 0.68 for a laboratory scale Falcon L40 equipped with a UF bowl (Kroll-Rabotin et al, 2011b). The need of a calibration constant has already been detailed extensively in Kroll-Rabotin et al (2011b): it actually only reflects the simplifications we have included in the model derivation such as:…”
Section: Physical Analysis and Hypothesesmentioning
confidence: 99%